129. LiaX, a Member of the LiaFSR System, is Essential for Cell Envelope Adaptation System in Enterococcus faecium. (15th December 2022) - Cecilia Tran, Truc; Panesso, Diana; Zhao, Audrey; khan, Ayesha; Axell-House, Dierdre B; Shamoo, Yousif; Arias, Cesar A
Abstract: Background: Daptomycin (DAP) is an important antibiotic for enterococci. Our previous studies identified LiaX as a surface-exposed protein that is a mediator of cell envelope homeostasis in Enterococcus faecalis ( Efs ) upon exposure to DAP via activation of the LiaFSR system. LiaX encodes for a soluble protein with an N-terminal of α-helices, and a C-terminus which is β-pleated sheets. Its role in E. faecium, a species of clinical relevance, remains unknown. In this work, we aim to elucidate the function of LiaX of E. faecium ( Efm ). Methods: We used the commensal strain of Efm TX1330RF (DAP minimum inhibitory concentration [MIC] 3 μg/ml), its Δ liaR derivative (TX1330RFΔ liaR [DAP MIC 0.125 μg/ml]) and targeted the liaX gene for mutagenesis. Using the PheS* counterselection system, we aimed to create a truncation or in-frame deletion of liaX . Mutants were characterized by determination of DAP MIC and visualization of anionic phospholipid domains by 10-N- nonyl -acridine orange (NAO). The nisin-controlled expression vector, pMSP3535, was used to express LiaX from Efm (LiaXTX1330RF ) in Efs host OG1RFΔ liaX, which lacks liaX . Expression of LiaX of Efs (LiaXOG1RF ) was used as a control. Results: In the presence of liaR, we were unable to create truncation or in-frame deletion of liaX after many attempts. In Efm TX1330RFΔ liaR, we successfully created an in-frame deletion of liaX, TX1330RFΔ liaRliaX (DAP MIC 0.125 μg/ml). NAO staining of all strains of TX1330RF, TX1330RFΔ liaR and its Δ liaX mutant showed localization of anionic phospholipid domains at septa of the cells. Interestingly, multiple attempts to complement liaR in TX1330RFΔ liaRliaX were also futile. NAO staining of Efs OG1RFΔ liaX demonstrated that anionic phospholipid microdomains redistributed away from septa. Expression of LiaXOG1RF in Efs OG1RFΔ liaX successfully restored microdomains to septal and polar regions of Efs while expression of LiaXTX1330RF did not show any significant difference in the fluorescence staining compared to its parental host ( Efs OG1RFΔ liaX ). Conclusion: Our findings suggest that LiaX has divergent functions as a mediator of cell envelope homeostasis in enterococci and may be essential in the Efm redponse to DAP. Efforts to elucidate its role in DAP resistance in Efm are ongoing. Disclosures: Cesar A. Arias, MD, PhD, Entasis Phramceuticals: Grant/Research Support|MeMed Diagnostics: Grant/Research Support|Merck: Grant/Research Support.